1984
DOI: 10.1080/15287398409530561
|View full text |Cite
|
Sign up to set email alerts
|

The health implications of increased manganese in the environment resulting from the combustion of fuel additives: A review of the literature

Abstract: Methylcyclopentadienyl manganese tricarbonyl (MMT) is effective in raising the octane level of gasoline and is currently used in Canada for that purpose in a maximal concentration of 18 mg Mn/l (slightly less than 0.07 g Mn/U.S. gal). It has been estimated that if MMT were used in all U.S. gasoline in these amounts, the median increase of Mn in ambient air would be not more than 0.05 microgram Mn/m3, with increments generally less than 0.5 microgram Mn/m3 along urban corridors. The scientific literature was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 68 publications
0
33
0
Order By: Relevance
“…All components from mobile sources increased in the fall and winter and were lower in spring and summer. Methylcyclopentadienyl manganese tricarbonyl (MMT) is an organic derivative of manganese (Mn) used in unleaded gasoline as an antiknock agent [16]. Its use has increased substantially and its combustion leads to the formation of oxides of manganese (99.9%), especially manganese tetraoxide or hausmannite (Mn 3 O 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…All components from mobile sources increased in the fall and winter and were lower in spring and summer. Methylcyclopentadienyl manganese tricarbonyl (MMT) is an organic derivative of manganese (Mn) used in unleaded gasoline as an antiknock agent [16]. Its use has increased substantially and its combustion leads to the formation of oxides of manganese (99.9%), especially manganese tetraoxide or hausmannite (Mn 3 O 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…This disease, known as manganism, begins as a loss of appetite, apathy, fatigue, psychotic behaviour, and clumsiness. At lower levels of exposure, delayed reaction time, poor hand-eye coordination, memory loss, and tremors have been reported (Mena 1974, Moran 1975, Tar Haar et al 1975, USEPA 1975, Pierson et al 1978, Barbeau 1984, Cooper 1984, Abbott 1987, Ethyl Corporation 1990. Experimental data on animals have shown that exposure to MMT produces severe injury to the kidneys, liver, lungs and the central nervous system (Komura andSakamoto 1992, U.S. Dept.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that one of the main sources of inorganic Mn contamination in the urban environment may be the combustion of fuel containing MMT (Joselow et al 1978, Davis et al 1988, Zayed and (Cooper 1984). 1994). Since 1974, medical studies have attempted to predict the contribution of Mn fi-om the combustion of W-containing fuels to the atmospheric Mn concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The additive was first developed in the 1950s by scientists at Ethyl Corp. and is marketed under the trade name HiTEC 3000-performance additive. 2 MMT was first used in Canada in 1976 as an antiknock agent in unleaded gasoline.…”
Section: Introductionmentioning
confidence: 99%